IN SILICO ASSESSMENT OF AMELIORATIVE EFFECTS OF POLYUNSATURATED FATTY ACID (PUFAS) FROM NAVICULA SALINICOLA AS AN INHIBITOR OF BENIGN PROSTATE HYPERPLASIA - FEBRINA, ELLIN; YULIANTINI, ANNE; KURNIA, DEWI; ASNAWI, AIYI (International Journal of Applied Pharmaceutics, 2023)
Objective: Benign prostatic hyperplasia (BPH) is a prevalent, non-cancerous condition affecting aging men worldwide. As an alternative approach to conventional treatment options, polyunsaturated fatty acids (PUFAs) have gained attention for their potential therapeutic effects on various health conditions. This study investigated the interaction of PUFAs obtained from Navicula salinicola with the macromolecule associated with BPH, represented by STAT3, that is involved in the androgen signaling pathway in BPH (PDB ID 6NJS), using molecular docking simulations. Methods: The docking simulations revealed the interaction patterns and binding affinities of 14 PUFAs with the amino acid residues of STAT3. The calculated binding energies and inhibition constants provided insights into the potential inhibitory effects of PUFAs on BPH. Results: Results indicated that g-linolenic acid exhibited a strong binding affinity, forming hydrogen bonds with ARG609 and hydrophobic interactions with VAL637 and PRO639, highlighting its potential as a potent inhibitor. Docosahexaenoic acid also showed favorable interactions with ARG609 and hydrophobic residues, suggesting its potential therapeutic relevance. Conclusion: g-Linolenic acid from N. salinicola exhibited a strong molecular interaction with STAT3.